Reflections through the lens: Participatory video with migrant domestic workers, asylum seekers and ethnic minorities. (November 2019) - Lin, Vivian Wenli; Ham, Julie; Gu, Guolin; Sunuwar, Merina; Luo, Chunya; Gil-Besada, Laura
Abstract: In this article, we explore the reflexive use of emotion in understanding emerging relational rhythms in participatory video. The focus of our analysis is the Visualizing the Voices of Migrant Women Workers project, which involved a series of eight video-making workshops from February–April 2017 in Hong Kong for over 40 domestic workers, asylum seekers, and ethnic minority participants. The emotions that were key to navigating relational rhythms central to this creative space were (1) feelings of discomfort to understand relations between the workshop participants and the facilitation team, (2) gratitude to assess the 'chemistry' or relations between workshop participants and (3) trepidation to re-write participants' relations with the city of Hong Kong. There is an important opportunity to explore the role of emotion in analysing relational rhythms in PV practice, in order to nurture creative solidarities and create new ethical potentialities. Highlights: Emotion is a key reflexive resource in understanding emerging relational rhythms in participatory video (PV). Negative emotions, such as discomfort and trepidation, can be an instructive part of the participatory video (PV) process. Analysis of relational rhythms can expand participatory video practice. Understanding participation as an assemblage of rhythms aids analyses of ethical potentiality (Springgay, 2016).